The concentration of lidocaine and mepivacaine measured in synovial fluid of different joints of horses after single intra-articular injection - Adler, Ditte M. T.; Jørgensen, Elin; Cornett, Claus (Frontiers in Veterinary Science, 2022)
Objective To determine the synovial fluid (SF) concentrations of lidocaine and mepivacaine after intra-articular injection with clinically relevant doses to the distal interphalangeal (DIP), metacarpophalangeal (MCP), middle carpal (MC) and tarsocrural (TC) joint at two different time points after injection in order to be able to . Further to comparecompare concentrations with previously established concentrations associated with cytotoxicity and antimicrobial activity. the measured concentrations with concentrations previously known to induce articular cell cytotoxicity and antimicrobial activity. Procedures In the first of two experiments, 20 joints (5 MC, 5 MCP, 10 DIP joints) of five horses under general anesthesia were injected with clinically referenced doses of 2% lidocaine. Simultaneously, the horses had 19 joints (5 MC, 5 MCP, 9 DIP joints) injected with clinically referenced doses of 2% mepivacaine. Synovial fluid samples were collected ~75 minutes after injection In experiment 2, 23 joints of 7 horses under standing sedation were injected with clinically referenced doses of 2% lidocaine. Similarly, the horses had 21 joints injected with 2% mepivacaine. Synovial fluid samples were collected ~230 minutes after injection The concentration of mepivacaine and lidocaine in the obtained SF samples was assessed using high-performance-liquid-chromatography with mass spectrometry detection (HPLC MS). Results Synovial fluid was obtained 6.8 ± 1.5 (experiment 1) and 23 ± 4.3 (experiment 2) minutes following intra-articular injection of mepivacaine and lidocaine. Synovial fluid concentrations of experiment 1 for lidocaine both Las and mepivaciane were 6.46-19.62 mg/mL (mean 11.96 ± SD 3.89 mg/mL) and 5.01-13.38 mg/mL (mean 8.18 ± SD 1.76 mg/mL), mg/mLrespectively. In experiment 2, concentrations were 2.94-10.40 mg/mL (mean 6.31± SD 2.23 mg/mL) for lidocaine and 2.10-8.70 mg/mL (mean 4.97 ± SD 1.77 mg/mL) 3-8 mg/mL.for mepivacaine. Conclusions and clinical relevance Intra-articular LA injections in horses resulted in SF concentrations above those previously associated with cytotoxic effects in vitro but also above those associated with beneficial antimicrobial activities. Local anesthetic concentration was 33-60% lower after 23 minutes (experiment 2) than after 7 minutes (experiment 1).